The theater experience - Wilson, Edwin (McGraw-Hill, 2004)
The ideal theater appreciation text for courses focusing on theater elements, The Theater Experience encourages students to be active theater-goers as they learn about the fundamentals of a production. By addressing the importance of the audience, Wilson brings the art of performance to life for students who may have little experience with the medium